2005
DOI: 10.1309/mgrx-lqg9-qvrv-vmcg
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Initial and Deeper Sections of Esophageal Biopsy Specimens for Detection of Intestinal Metaplasia

Abstract: There are wide variations in the preparation of histologic sections from endoscopic esophageal biopsy specimens. We evaluated serial step sections from 261 esophageal or gastroesophageal junction biopsies at 4 levels to determine the first level at which goblet cell metaplasia (GCM) was detected. Deeper step sections of 152 paraffin blocks also were obtained to determine whether additional sections are useful in detecting GCM not seen in initial levels. GCM was identified in 95.3% of blocks in 3 levels. GCM wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 9 publications
0
14
0
Order By: Relevance
“…[2] Various studies have suggested opting for deeper sections in case of incorrect orientation & unclear histological findings in initial sections. [8,11] Sampling error…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[2] Various studies have suggested opting for deeper sections in case of incorrect orientation & unclear histological findings in initial sections. [8,11] Sampling error…”
Section: Discussionmentioning
confidence: 99%
“…• Initial sections when obtained are superficial and undiagnostic [2] • To identify positive areas that could contribute to a proper diagnosis and rule out certain diagnosis [2,4] • To avoid diagnostic error and subsequent malpractice claims [5] • To enhance sensitivity & diagnostic accuracy [2,6,7] • Disclosing additional pathological findings & hidden malignancies [1,2] • Orientation & plane of sectioning of the tissue specimen pose problems [8,9] labelling of sections.) [1] • Increased supply costs for staining materials, glass slides, etc., and the costs for an Increased storage volume must be considered [1] • Delay in dispatching the report [2] The studies undertaken emphasizing its importance is sparse.…”
Section: Advantages Of Step Verses Serial Sectionsmentioning
confidence: 99%
“…When an initial section is non‐diagnostic, it is customary for the dermatopathologist to order one or more deeper/level sections (retrospective deeper sections), which may cause a delay in turn‐around‐time. To prevent this delay, some laboratories order deeper sections in advance for some or all biopsies (prospective deeper sections) . Because many biopsies do not require deeper sections, however, this leads to wasted time, cost and materials.…”
Section: Introductionmentioning
confidence: 99%
“…Prior studies have investigated the diagnostic utility of deeper sections in small specimens from a variety of organs, including the esophagus, colon, prostate, breast and cervix . In cutaneous specimens, research has been limited and has produced mixed results .…”
Section: Introductionmentioning
confidence: 99%
“…However, recuts and additional sections (AS) have drawbacks, including increased processing costs and increased turnaround times. Multiple studies have assessed the utility of recuts and levels in improving diagnostic accuracy [4][5][6][7][8] ; however, the diagnostic utility of "additional tissue sections" in a surgical pathology specimen has not been completely elucidated.…”
Section: Introductionmentioning
confidence: 99%